The Artificial Body in Fashion and Art : Marionettes, Models and Mannequins. - Geczy, Adam (Bloomsbury Publishing, 2016)
Artificial bodies constructed in human likeness, from uncanny automatons to mechanical dolls, have long played a complex and subtle role in human identity and culture. This book takes a range of these bodies, from antiquity to the present day, to explore how we seek out echoes, caricatures and replications of ourselves in order to make sense of the complex world in which we live. Packed with case studies, from the commedia del'arte to Hans Bellmer, and the work of Andre Courreges to the 1980s supermodel, this volume explores the divide between the "real" and the constructed. Arguing that the body "other" plays a crucial role in the formation of the self physically and psychologically, leading scholar Adam Geczy contends that the "natural" body has been replaced by a series of imaginary archetypes in our post-modern world, central to which is the figure of the doll. The Artificial Body in Fashion and Art provides a much-needed synthesis of constructed bodies across time and place, drawing on fashion theory, theatre studies and material culture, to explore what the body means in the realms of identity, gender, performance and art